Development and validation of an instrument for nursing consultation with pediatric patients in the preoperative period - Paloma Gonçalves Martins Acioly; Eny Dórea Paiva; Adriana Teixeira Reis; Tatiana de Oliveira Gomes; Luciana Rodrigues da Silva; Liliane Faria da Silva (Revista da Escola de Enfermagem da USP, 2022)
ABSTRACT Objective: To develop and validate an instrument for nursing consultation with pediatric patients in the preoperative period. Method: This is a methodological study, consisting of five steps: identification of nursing diagnoses, discussion and evaluation of diagnoses with nurses from the institution, instrument development, instrument content validation with experts through the Delphi Technique, and instrument restructuring. The Nursing Minimum Data Set, Wanda Horta’s human needs, and the NANDA-NOC-NIC connections were used as theoretical framework. Results: In its final version, the instrument includes an assessment of psychobiological, psychosocial, and psychospiritual human needs, 38 nursing diagnoses, 65 nursing interventions, 113 nursing activities, and 62 nursing outcomes. The instrument obtained a content validity index between 0.90 and 1.0 in the first round, and suggestions, validated in the second round, obtained agreement from 70 to 100%. Conclusion: The instrument developed can be a tool for use in nursing consultations in the preoperative period for children, providing greater assertiveness to nursing actions for this clientele.